European Society of Coloproctology Core Outcome Set for haemorrhoidal disease: an international Delphi study among healthcare professionals. (8th February 2019) - van Tol, R. R.; Kimman, M. L.; Melenhorst, J.; Stassen, L. P. S.; Dirksen, C. D.; Breukink, S. O.; ,
Abstract: Aim: There is considerable heterogeneity in outcomes in studies reporting on the treatment of haemorrhoidal disease (HD). The aim of this study was to develop a Core Outcome Set (COS) for HD in cooperation with the European Society of Coloproctology. Method: A Delphi study was performed according to the Outcome Measures in Rheumatology (OMERACT) methodology. In total 38 healthcare professionals and 30 patients were invited to the panel. Previously, 10 outcome domains and 59 outcomes were identified through a systematic literature review. In this study, these domains and outcomes were formed into one questionnaire for healthcare professionals and a separate questionnaire for patients. Sequential questionnaire rounds prioritizing the domains and outcomes were conducted. Panel members were asked to rate the appropriateness of each domain and outcome on a nine‐point Likert scale. During a face‐to‐face meeting, healthcare professionals agreed on the primary and secondary end‐points of the COS for HD. Finally, a short survey was sent to the healthcare professionals in order to reach consensus on how the chosen end‐points should be assessed and at which time points. Results: The response rate in questionnaire round 1 for healthcare professionals was 44.7% ( n = 17). Sixteen out of 17 healthcare professionals also completed the questionnaire in round 2. The response rate for the patient questionnaire was 60% ( n = 18). Seventeen healthcare professionals participated in the face‐to‐face meeting. The questionnaire rounds did not result in a clear‐cut selection of primary and secondary end‐points. Most domains and outcomes were considered important, and only three outcomes were excluded. During the face‐to‐face meeting, agreement was reached to select the domain 'symptoms' as primary end‐point, and 'complications', 'recurrence' and 'patient satisfaction' as secondary end‐points in the COS for HD. Furthermore, consensus was reached that the domain 'symptoms' should be a patient reported outcome measure and should include the outcomes 'pain' and 'prolapse', 'itching', 'soiling' and 'blood loss'. The domain 'complications' should include the outcomes 'incontinence', 'abscess', 'urinary retention', 'anal stenosis' and 'fistula'. Consensus was reached to use 'reappearance of initial symptoms' as reported by the patient to define recurrence. During an additional short survey, consensus was reached that 'incontinence' should be assessed by the Wexner Fecal Incontinence Score, 'abscess' by physical examination, 'urinary retention' by ultrasonography, 'anal stenosis' by physical examination, and 'fistula' by physical examination and MR imaging if inconclusive. During follow‐up, the outcome 'symptoms' should be assessed at baseline, 7 days, 6 weeks and 1 year post‐procedure. The outcomes 'abscess' and 'urinary retention' should be assessed 7 days post‐procedure and 'incontinence', 'anal stenosis' and 'fistula' 1 year post‐procedure. Conclusions: We developed the first European Society of Coloproctology COS for HD based on an international Delphi study among healthcare professionals. The next step is to incorporate the patients' perspective in the COS. Use of this COS may improve the quality and uniformity of future research and enhance the analysis of evidence.